Apparent half-lives of sugar transport proteins in Saccharomyces cerevisiae - Alonso, A; Kotyk, A (Folia microbiologica, 1978)
Using incubation in the presence of 0.4 mM cycloheximide the half-lives of the principal membrane transport proteins in baker's yeast were found to be: more than 24 h for the constitutive glucose carrier, 2.2 h for the inducible galactose carrier, 1.2 h for the inducible maltose carrier and 0.8 h for the inducible alpha-methyl-D-glucoside carrier. The distinct nature of the two last-named carriers was thus supported. De-induction of the galactose carrier was enhanced in the presence of glucose plus cycloheximide but not of either substance alone. Chloramphenicol suppressed all effects of cycloheximide. In contrast to the enzymes of galactose metabolism, the induction of the glactose carrier was not under the control of a mitochondrial factor and took place in a rho-mutant. The system induced by maltose but not the one induced by alpha-methyl-D-glucoside was de-induced rapidly by the intervention of a cytoplasm-synthesized protein.
Keywords: Half-Life; Methylglucosides; Saccharomyces cerevisiae; galaktosa; methylglukosidy; metabolismus sacharidů; Carbohydrate Metabolism; Carrier Proteins; Galactose; chloramfenikol; transportní proteiny; cykloheximid; Cycloheximide; Chloramphenicol; glukosa; Glucose; poločas